The health policy response to COVID-19 in Malawi. Issue 5 (18th May 2021) - Mzumara, Grace W; Chawani, Marlen; Sakala, Melody; Mwandira, Lily; Phiri, Elias; Milanzi, Edith; Phiri, Mphatso Dennis; Kazanga, Isabel; O'Byrne, Thomasena; Zulu, Eliya M; Divala, Titus; Iroh Tam, Pui-Ying; et al.
Abstract : Malawi declared a state of national disaster due to the COVID-19 pandemic on 20th March 2020 and registered its first confirmed coronavirus case on the 2 April 2020. The aim of this paper was to document policy decisions made in response to the COVID-19 pandemic from January to August 2020. We reviewed policy documents from the Public Health Institute of Malawi, the Malawi Gazette, the Malawi Ministry of Health and Population and the University of Oxford Coronavirus Government Response Tracker. We found that the Malawi response to the COVID-19 pandemic was multisectoral and implemented through 15 focused working groups termed clusters. Each cluster was charged with providing policy direction in their own area of focus. All clusters then fed into one central committee for major decisions and reporting to head of state. Key policies identified during the review include international travel ban, school closures at all levels, cancellation of public events, decongesting workplaces and public transport, and mandatory face coverings and a testing policy covering symptomatic people. Supportive interventions included risk communication and community engagement in multiple languages and over a variety of mediums, efforts to improve access to water, sanitation, nutrition and unconditional social-cash transfers for poor urban and rural households.